1998
DOI: 10.1021/la980257z
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Attachment of Cell-Adhesive, (Arg-Gly-Asp)-Containing Peptides to Titanium Surfaces

Abstract: A three-step reaction procedure was applied to introduce RGD-containing peptides on the titanium surface. Water-vapor-plasma-pretreated titanium surfaces were first silanized with (3-aminopropyl)triethoxysilane, resulting in a multilayer film of poly(3-aminopropyl)siloxane. In a second reaction step, the free primary amino groups were linked to one of the three hetero-cross-linkers: N-succinimidyl-6maleimidylhexanoate, N-succinimidyl-3-maleimidylpropionate, and N-succinimidyl trans-4-(maleimidylmethyl)cyclohex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
289
3
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(319 citation statements)
references
References 39 publications
22
289
3
5
Order By: Relevance
“…Silanization has been successfully used to functionalize metallic biomaterials with bioactive 8,[23][24][25][26] . This method of surface modification allows the covalent attachment of peptides and proteins through the use of organofunctional alkoxysilane molecules that react with hydroxyl groups present at the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silanization has been successfully used to functionalize metallic biomaterials with bioactive 8,[23][24][25][26] . This method of surface modification allows the covalent attachment of peptides and proteins through the use of organofunctional alkoxysilane molecules that react with hydroxyl groups present at the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, 3-aminopropyltriethoxysilane (APTES) has been widely used to covalently attach cell adhesive peptides (i.e. RGD peptides) [25][26][27] , and more recently AMPs 8,28,29 , onto titanium surfaces. The binding of these biomolecules onto aminosilanized samples often requires the reaction with crosslinking agents (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The most common ones use silane coupling agents that react with the oxide layer formed on metal surfaces. [21][22][23][24][25][26][27] In most cases, the silane coupling agent consists of a trimethoxy or triethoxy silane where the fourth bond of the silane molecule is an organo-functional group that can be further reacted to attach a variety of organic compounds or polymers. The methoxy or ethoxy groups hydrolyze, leaving the silanol to react with the metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant work has been done to attach proteins and peptides to metal oxide particles 21 and silicon oxide on Si wafers, 26 relatively little research has been reported on attachment of polypeptides to macroscopic metallic surfaces. 23,24,26,27,50 -53 With respect to short peptides, Xiao et al 27 attached an RGDcontaining peptide to titanium using aminopropyl silane and maleimide chemistry. Rezania et al 26 attached the RGD sequence to quartz using similar chemistry, and showed that the RGD retained its activity in promoting the attachment and spread of rat calvaria osteoblast-like cells.…”
Section: Introductionmentioning
confidence: 99%
“…SGGRGD) hence confirming the presence of the oligopeptides at the surface (Table 1, silane+peptide). Furthermore, the deconvolution of the C 1s spectrum for biofunctionalized surfaces showed an increase in both peaks (C2 /C3) corresponding to the C-N, C-OH and C = O groups derived from peptides and, also, the appearance extra peak due to the peptide characteristic guanadine and O=C-N (binding energy at 288.9 eV) bonds (see table 2, silane+peptide) [46,[52][53][54].…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%